Face Distortion Aftereffects in Personally Familiar, Famous, and Unfamiliar Faces - Walton, Billy R.; Hills, Peter J. (Frontiers in Psychology, 2012)
Abstract The internal face prototype is thought to be a construction of the average of every previously viewed face (Schwaninger, Carbon, & Leder, 2003). However, the influence of the most frequently encountered faces (i.e., personally familiar faces) has been generally understated. The current research explored the face distortion after effect in unfamiliar and personally familiar faces (each subject’s parent). Twelve adult participants rated the distortion levels (distorted by shifting the eyes in the vertical axis) of a series of images that included unfamiliar and personally familiar faces. The number of faces perceived to be distorted was measured pre- and post-adaptation to the most extreme distortion. Participants were adapted to either an unfamiliar or personally familiar face. The results indicate that adaptation transferred from unfamiliar faces to personally familiar faces more so than the converse. These results are indicative of representation differences between unfamiliar faces and personally familiar faces.